2022
DOI: 10.1111/sltb.12850
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary, temporary, out‐of‐home firearm storage: A qualitative study of stakeholder views

Abstract: Background Reducing firearm access during times of risk is a key component of suicide prevention, including the person at risk voluntarily, temporarily storing firearms outside the home. However, this approach relies on the participation of storage providers (ranges/retailers and law enforcement agencies (LEAs)). Our objective was to describe stakeholders' views and experiences surrounding voluntary, temporary out‐of‐home firearm storage for suicide prevention. Method We conducted individual interviews with (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…Previous studies have described concerns of law enforcement agencies and retailers/ranges participating in out-of-home storage programs including logistical and liability concerns (Betz et al 2022). Our study showed similar concerns of those with access to firearms about out-of-home storage programs.…”
Section: Discussionsupporting
confidence: 75%
“…Previous studies have described concerns of law enforcement agencies and retailers/ranges participating in out-of-home storage programs including logistical and liability concerns (Betz et al 2022). Our study showed similar concerns of those with access to firearms about out-of-home storage programs.…”
Section: Discussionsupporting
confidence: 75%
“…Interviews were analyzed using a team-based mixed inductive/ deductive method similar to that used previously by members of our group. 16,[21][22][23][24] This approach includes a mix of analytic methods, including constant comparative, grounded theory, and content analysis methods. 25 Coding was conducted by the interviewers (BW, CEK) who have masters and doctoral level training in qualitative research methods.…”
Section: Discussionmentioning
confidence: 99%
“…The parent study was designed to examine perspectives around out-of-home, voluntary, temporary firearm storage 17. We recruited individuals through social media, list serves, emails to network associates and snowball sampling from participants.…”
Section: Methodsmentioning
confidence: 99%